Analisis Steganography Terhadap Keamanan Data - Juman, Kundang Karsono (JIK: Jurnal Ilmu Komputer, 2008)
The computer security system includes security data this time able to issue demand. Steganography is the art of concealing the existence of information within seemingly innocuous carriers. Steganography can be viewed as akin to cryptography. Both have been used throughout recorded history as means to protect information. At times these two technologies seem to converge while the objectives of the two differ. Cryptographic techniques "scramble" messages so if intercepted, the messages cannot be understood. Steganography, in an essence. The Implementation steganography in side data security with: Learning to the concept computer security system, to be understand steganography, and to knows in implementation steganography in the data securityKeywords: The Computer Security, Data Security, Steganography Method Data Security and Media